Novel Checkpoints and Cosignaling Molecules in Cancer Immunotherapy. Issue 1 (January 2017) - Giuroiu, Iulia; Weber, Jeffrey
Abstract : Abstract: The recent demonstration of the antitumor efficacy of checkpoint protein inhibition has resulted in the approval of blocking antibodies against the programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) pathway in multiple different histologic findings. Therapeutic successes with PD-1/PD-L1 antibodies in melanoma and lung cancer have been followed by approvals in bladder, renal, and head and neck cancers and Hodgkin lymphoma, with others undoubtedly to come. However, PD-1 is only one of many checkpoints and agonistic regulatory molecules expressed on T cells by which maintenance of the balance between costimulatory and coinhibitory signaling pathways is perturbed in cancer. The manipulation of many of these molecules in cancer patients might be associated with clinical benefit. The majority of the T-cell cosignaling receptors belong to either the immunoglobulin superfamily or the tumor necrosis factor receptor superfamily. A total of 29 immunoglobulin superfamily and 26 tumor necrosis factor receptor superfamily cosignaling receptors have been identified that are expressed on T cells, providing fertile ground for development of inhibitory or agonistic antibodies and small molecules as cancer therapeutics. In the current work, we focus on some of the most promising new checkpoints and agonistic or cosignaling molecules that are in early clinical development as single agents or in combinations with PD-1/PD-L1, cytotoxic T-lymphocyte-associated protein 4 blockade, or chemotherapy with an emphasis on those that have reached the clinic and on important targets that are in late preclinical development.